2016
DOI: 10.1002/2015gc006062
|View full text |Cite
|
Sign up to set email alerts
|

Environmental rock‐magnetism of Cenozoic red clay in the South Pacific Gyre

Abstract: Nonfossiliferous red clay can be used for elucidating long‐range environmental changes, although such studies were limited so far because of the difficulty in precise age estimation and extremely low sedimentation rates. We conducted an environmental rock‐magnetic study of Cenozoic red clay at the Integrated Ocean Drilling Program Site U1365 in the South Pacific Gyre. Magnetostratigraphy could be established only above ∼6 m below the seafloor (mbsf) (∼5 Ma). Below ∼6 mbsf, the ages of the cores were transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 61 publications
(135 reference statements)
4
22
0
Order By: Relevance
“…This is consistent with the TEM images showing that the dominant magnetofossil morphology is equant octahedra. The L and M components with mean coercivities and DPs similar to those observed in core MR1402‐PC1 are commonly observed in pelagic sediments in the Pacific and Indian Oceans, and the M component is considered to be carried by maghemite of probably terrigenous origin (Roberts et al, ; Shimono & Yamazaki, ; Yamazaki, ; Yamazaki, ; Yamazaki & Ikehara, ). The contribution of the M component is a little smaller in the deeper part of the core (Figure ), which is consistent with the increased k ARM /SIRM ratios suggesting a decreased terrigenous input.…”
Section: Resultsmentioning
confidence: 89%
“…This is consistent with the TEM images showing that the dominant magnetofossil morphology is equant octahedra. The L and M components with mean coercivities and DPs similar to those observed in core MR1402‐PC1 are commonly observed in pelagic sediments in the Pacific and Indian Oceans, and the M component is considered to be carried by maghemite of probably terrigenous origin (Roberts et al, ; Shimono & Yamazaki, ; Yamazaki, ; Yamazaki, ; Yamazaki & Ikehara, ). The contribution of the M component is a little smaller in the deeper part of the core (Figure ), which is consistent with the increased k ARM /SIRM ratios suggesting a decreased terrigenous input.…”
Section: Resultsmentioning
confidence: 89%
“…The FORC distributions of the broad component are interpreted to be carried by a mixture of interacting SD, PSD, and MD grains [Roberts et al, 2000;Pike et al, 2001;Muxworthy and Dunlop, 2002;Roberts et al, 2014]. The magnetic grains that constitute the component(s) with broad vertical spread on the FORC diagrams are inferred to have terrigenous origin [Yamazaki, 2008;Yamazaki and Ikehara, 2012;Shimono and Yamazaki, 2016]. It is hence considered that the magnetic mineral assemblages of the studied sediments are a mixture of biogenic and terrigenous components.…”
Section: Resultsmentioning
confidence: 96%
“…It is hence considered that the magnetic mineral assemblages of the studied sediments are a mixture of biogenic and terrigenous components. The broad component in the studied sediments is larger than that from other deep‐sea sediments in the Pacific and Indian Oceans [ Yamazaki , ; Yamazaki and Ikehara , ; Yamazaki and Shimono , ; Shimono and Yamazaki , ]. The larger terrigenous component, which is consistent with the relatively low k ARM /SIRM ratios of the sediments, probably indicates the proximity of the studied cores to terrigenous sediment sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on samples from the top 15 m of Hole U1366C that covers Subunit Ia, Ib, and Ic. At Site U1365 which is ~ 900 km west from Site U1366, Shimono and Yamazaki (2016) reported that magnetism of bulk sediments is largely controlled by magnetofossils, especially in sediments older than ~ 23 Ma.…”
Section: Samples and Geological Backgroundmentioning
confidence: 99%